1934
DOI: 10.1021/ja01316a011
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption of Nitrogen by Iron Synthetic Ammonia Catalysts

Abstract: Adsorption of Nitrogen by Iron Ammonia Catalysts 3f> were carried out in an unsilvered Pyrex Dewar of about 250 cc. capacity, surrounded by an eutectic mixture of CaCla-HjO. A rubber stopper covered with tin foil closed the neck of the Dewar. Through this stopper projected the thermocouple tube, a hand stirrer of glass and a tube for admitting nitrogen or dry air. It was found best to employ a mixture of about 3 parts of carbon tetrachloride to 1 part of methanol, by weight, since this gave a mixture which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

1960
1960
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(58 citation statements)
references
References 0 publications
3
54
1
Order By: Relevance
“…Complete nitrogen adsorption-desorption isotherms for the clay materials at 78 ~ were obtained using a volumetric apparatus based on the original apparatus of Emmett and Brunauer (1934) and incorporating many 8* of the refinements suggested by Harkins and Jura (1944) and Joyner (1949).…”
Section: (B) Low Temperature Nitrogen Sorption Isothermsmentioning
confidence: 99%
“…Complete nitrogen adsorption-desorption isotherms for the clay materials at 78 ~ were obtained using a volumetric apparatus based on the original apparatus of Emmett and Brunauer (1934) and incorporating many 8* of the refinements suggested by Harkins and Jura (1944) and Joyner (1949).…”
Section: (B) Low Temperature Nitrogen Sorption Isothermsmentioning
confidence: 99%
“…[29][30][31][32][33] However, because of the higher price of Ru and its shorter catalytic lifetime, the dominance of iron-based catalysts has only recently been challenged by promoted Ru catalysts. [34][35][36] In the 1930s, Emmett et al 37,38 found strong experimental evidence that N 2 dissociation over Fe catalysts is the ratelimiting step for ammonia synthesis under industrially relevant conditions. The improvements of surface science techniques made since the late 1970s have further strengthened this view.…”
Section: Introductionmentioning
confidence: 99%
“…The AI-containing phases have been interpreted as Ah03 segregated to the space between the Fe-crystallites based on evidence from chemisorption measurements [163] and X-ray powder diffraction studies [164]; as Al20 3 and FeAh04 based on evidence from EM and X-ray powder diffraction studies [48]; or as FeAl20 4 present as paracrystalline defects in the Fe crystallites based on evidence from secondary ion mass spectroscopy and Mossbauer studies [50,154,165,166]. The presence of FeAl20 4 as paracrystalline defects has been challenged on the basis of Mossbauer spectroscopic studies [112,165].…”
Section: Aluminummentioning
confidence: 99%